The care offered by nurses to elders with coronary artery disease from the perspective of Transitions Theory - Cláudia Fernanda Trindade Silva; Larissa Chaves Pedreira; Juliana Bezerra do Amaral; Fernanda Carneiro Mussi; Maria Antonia Martorell-Poveda; Monaliza Lemos de Souza (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To analyze the planning and implementation of the care offered by nurses to elders with coronary disease during the hospital-house transition. Methods: Qualitative research that used the Transitions Theory as a theoretical reference. The participants were 12 nurses who work in a hospital that specializes in cardiology, in the city of Salvador-BA. A semistructured interview was carried out from January to February 2018, and the data was analyzed using the Content Analysis technique. Results: Transition care takes place on the day of discharge. The presence of the family was found to be a facilitator; low adherence, poor financial situations, the low educational levels inhibited its implementation. The rehospitalization is an indicator of the results of the transition of care. Final considerations: The planning and implementation of transition care is not effective. It must provide safety in the management of self-care in the home of elders with coronary disease and their families.